Cultural Evolution
XV, 269 p.
Keywords: Drawing on Kent Flannery's forty years of cross-cultural research in the area, the contributors to this collection reflect the current diversity of contemporary approaches to the study of cultural evolutionary processes. Collectively the volume expresses the richness of the issues being investigated by comparative theorists interested in long-term change, as well as the wide variety of data, approaches, and ideas that researchers are employing to examine these questions.